Zasada prawdy materialnej a prawo do prywatności w polskim procesie karnym - Dobrzańska, Sara (Wydawnictwo Naukowe UAM, 2019)
Przedmiotem niniejszego artykułu jest przybliżenie relacji jaka zachodzi między obowiązywaniem w polskim procesie karnym zasady prawdy materialnej a ochroną prawa do prywatności jego uczestników. Konieczność poczynienia przez organy procesowe prawdziwych ustaleń faktycznych rodzi bowiem ryzyko ingerencji w sferę prywatną jednostek, które w różnych rolach, biorą udział w postępowaniu karnym. Instytucjami istotnymi, z punktu widzenia realizacji dyrektyw wynikających z zasady prawdy materialnej, dla ochrony prawa do prywatności, są przede wszystkim przesłuchanie świadka, przeszukanie oraz oględziny i to ich szersza analiza, w kontekście potencjalnych ograniczeń, jakich doznaje zasada prawdy materialnej, z uwagi na obowiązek poszanowania prawa do prywatności, stanowi przedmiot rozważań niniejszego artykułu.

The subject matter of this article is to present the relationship between the validity of the principle of material truth in the Polish criminal proceedings and the protection of the right to privacy of their participants. The necessity for real procedural arrangements to be made by judicial bodies creates a risk of interference in the private sphere of individuals who take part in criminal proceedings playing various roles in the same time. In terms of implementation of directives resulting from the principle of substantive truth in order to protect the right to privacy, the essential institutions are as follows: hearing a witness, search and inspection, and its broader analysis, within the context of potential limitations of the principle of material truth, due to the obligation to respect the right to privacy, which in general are the subject matter of this article.
The principle of material truth and the right to privacy in the Polish criminal proceedings
Keywords: proces karny; criminal proceedings; prawda materialna; material truth; prawo do prywatności; the right to privacy